Back to futures. (28th February 2022) - PRUIKSMA, KLAAS; PFENNING, FRANK
Abstract: Common approaches to concurrent programming begin with languages whose semantics are naturally sequential and add new constructs that provide limited access to concurrency, as exemplified by futures . This approach has been quite successful, but often does not provide a satisfactory theoretical backing for the concurrency constructs, and it can be difficult to give a good semantics that allows a programmer to use more than one of these constructs at a time. We take a different approach, starting with a concurrent language based on a Curry–Howard interpretation of adjoint logic, to which we add three atomic primitives that allow us to encode sequential composition and various forms of synchronization. The resulting language is highly expressive, allowing us to encode futures, fork/join parallelism, and monadic concurrency in the same framework. Notably, since our language is based on adjoint logic, we are able to give a formal account of linear futures, which have been used in complexity analysis by Blelloch and Reid-Miller. The uniformity of this approach means that we can similarly work with many of the other concurrency primitives in a linear fashion, and that we can mix several of these forms of concurrency in the same program to serve different purposes.